Neural Tube Defects And Role Of Folic Acid - DIVYA AGRAWAL; BISWA BHUSAN MOHANTY; SANJAY KUMAR; SUDHANSHU SEKHAR MISHRA (International Journal of Pharma and Bio Sciences, 2012)
Neural tube defects (NTDs) are a group of congenital malformations with worldwide distribution and complex etiopathogenesis. These are one of the commonest birth defects with high incidence in India. Animal studies indicate that there may be four sites of initiation of neural tube closure (NTC). Selective involvement of these sites may lead to defects varying from anencephaly to spina bifida. Genetic, nutritional and teratogenic mechanisms have been implicated in the pathogenesis of NTDs. Based on animal studies, epidemiologic studies and intervention trials, maternal folic acid is known to be protective for NTDs, primarily spina bifida and anencephaly. To reduce the risk of NTDs, the US Food and Drug Administration mandated that all enriched cereal grain products be fortified with folic acid as of January 1998. Recent data demonstrated that this public health action is associated with increased blood folate levels among women of child bearing age and that the occurrence of spina bifida has decreased by 20%. Birth defect prevention includes a recommended daily dose of 400 µg synthetic folic acid.